2014
DOI: 10.1890/13-1571.1
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in liana abundance and forest dynamics in undisturbed Amazonian forests

Abstract: Lianas (climbing woody vines) are important structural parasites of tropical trees and may be increasing in abundance in response to global-change drivers. We assessed long-term (-14-year) changes in liana abundance and forest dynamics within 36 1-ha permanent plots spanning -600 km2 of undisturbed rainforest in central Amazonia. Within each plot, we counted each liana stem (> or = 2 cm diameter) and measured its diameter at 1.3 m height, and then used these data to estimate liana aboveground biomass. An initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 59 publications
(122 reference statements)
4
114
1
3
Order By: Relevance
“…4). This difference suggests that the changes in liana abundance in intact forest might have had a different cause than those in fragments: one not directly related to increasing forest dynamics, such as, for instance, rising CO 2 levels (there is no evidence that droughts increased during our study; Laurance et al 2014). In fragments, however, a combination of elevated tree mortality (Fig.…”
Section: Changes In Forest Fragmentsmentioning
confidence: 66%
See 1 more Smart Citation
“…4). This difference suggests that the changes in liana abundance in intact forest might have had a different cause than those in fragments: one not directly related to increasing forest dynamics, such as, for instance, rising CO 2 levels (there is no evidence that droughts increased during our study; Laurance et al 2014). In fragments, however, a combination of elevated tree mortality (Fig.…”
Section: Changes In Forest Fragmentsmentioning
confidence: 66%
“…By physically stressing trees and competing for light, nutrients, and water, liana infestations can reduce tree growth, fecundity, survival, and recruitment (Putz 1984, Stevens 1987, Schnitzer et al 2000, Schnitzer and Carson 2010, Yorke et al 2013. As a result, lianas can have a considerable impact on forest dynamics, tree-species composition, and carbon storage , 2014, Schnitzer and Bongers 2002, Ko¨rner 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Liana thus has the potential to alter forest C storage, by reducing tree growth and survival [18]. It has been widely reported that tree aboveground biomass is negatively correlated with liana abundance [10,18,35], which indicates the increase in liana under climate change [36,37] may reduce C storage of forest by the inhibition of growth. However, the positive effects of liana on litter accumulation and SOC found in this study may temper the negative influence of liana on forest C storage at the ecosystem level.…”
Section: Implications For Forest C Storage and Ecological Restorationmentioning
confidence: 99%
“…Well-developed root systems of lianas [16] could impact soil physicochemical property, such as soil texture and C substrate availability during root growth and turnover [17,18]. For example, it has been found that soil organic C (SOC) and total nitrogen (TN) content were increased because of root turnover and rhizodeposition in an agricultural vineyard [19].…”
Section: Introductionmentioning
confidence: 99%
“…O aumento da abundância de lianas tem um efeito negativo no aumento da biomassa arbórea, reduzindo o crescimento e sobrevivência das árvores, assim como uma redução do armazenamento de carbono da floresta (Laurance et al 2014, Schnitzer & Bonger 2011, Phillips et al 2002. Como mencionado por Laurance et al (2014), três hipóteses têm sido propostas para explicar o aumento da abundância de lianas nas florestas maduras. A primeira é referente às estações secas que podem ter aumentado nas regiões tropicais, possibilitando uma mudança regional e global do clima.…”
Section: Ecologia De Lianasunclassified